2022
DOI: 10.1063/5.0088351
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ion partitioning on an oscillatory electro-osmotic flow on solute transport process of fractional Jeffrey fluid through polyelectrolyte-coated nanopore with reversible wall reaction

Abstract: The ion-partitioning effects on solute transport phenomena of time-periodic electro-osmotic flow in fractional Jeffrey fluid are investigated through a polyelectrolyte layer (PEL)-coated conical nanopore within a reactive wall whose ends are connected with two large reservoirs. By considering the ion-partitioning effects, analytical solutions for the induced potential and the axial velocity are presented, respectively, from the modified Poisson–Boltzmann equation and the Cauchy momentum equation with the prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…In their study, they considered two reactions at the fluid-wall interface. Koner et al (2022) studied the effects of ion-partitioning on solute transport phenomena of time-periodic EOF in fractional Jeffrey fluid through a PEL-coated conical nanopore within a reactive wall whose ends are connected with two large reservoirs. They found that introducing the fluid elastic properties, the important changes in the mass transport characteristics are evidenced in comparison with electro-osmosis flow of a Newtonian fluid under an AC electric field.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, they considered two reactions at the fluid-wall interface. Koner et al (2022) studied the effects of ion-partitioning on solute transport phenomena of time-periodic EOF in fractional Jeffrey fluid through a PEL-coated conical nanopore within a reactive wall whose ends are connected with two large reservoirs. They found that introducing the fluid elastic properties, the important changes in the mass transport characteristics are evidenced in comparison with electro-osmosis flow of a Newtonian fluid under an AC electric field.…”
Section: Introductionmentioning
confidence: 99%